Quality evaluation of onion irradiated in Argentina and stored in Brazil - Melges Walder, Julio Marcos; Curzio, Osvaldo Alfredo; Croci, Clara Ana; Domarco, Rachel Elisabeth; Fillet Spoto, Marta Helena; Blumer, Lucimara (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this study was to evaluate the quality of the onion cultivar Valenciana Sintética 14, irradiated with 60 Gy and sent by road from Buenos Aires, Argentina, to Piracicaba, SP, Brazil. The irradiated onion lot (20 bags of 20 kg each) and the control lot (20 bags of 20 kg each) were stored up to six months at 20ºC-28ºC and RH ranging from 50% to 100%. Quality control was made every month by physical, chemical and sensorial analysis. The radiation treatment reduced the weight loss of the bulbs and preserved the high percentage of marketable bulbs without affecting the sensorial properties. After 180 days of storage, the weight loss of unirradiated samples was 32%, significantly higher than irradiated samples (13%). The percentage of marketable bulbs was 92.3% for irradiated samples, and 52.3% for unirradiated samples.